D.I. Ray. Season one [videorecording (DVD)] - Sondhi, Maya (PBS, 2023)
DI Rachita Ray is promoted to join a homicide investigation. When she's told the murder is a 'Culturally Specific Homicide,' it makes her suspect she's been chosen for her ethnicity rather than her ability. However, Rachita sticks to the case, determined to find the killer by delving deep into the dangerous world of organized crime, as well as calling out the obvious biases her colleagues are bringing to the investigation.